Three theses on the historiography and ontology of Ferrater Mora - Casanovas, Pompeu (Journal of Catalan Intellectual History, 2014)
This paper advances three theses on the link between ontology and history in Ferrater Mora’s works: (i) his intellectual history is a second-order semantic history, (ii) his ontology may be defined as a second-order hermeneutics, and (iii) his philosophy (which he called integrationism) consists of a second-order dialogue that, despite its limitations, comes to make sense within the latest generation of the Web. The paper also considers the role of computational ontologies in the management and organisation of philosophical contents. key words Ferrater Mora, ontology, ontologies, intellectual history, philosophy of history, integrationism.